A novel case of cutaneous squamous cell carcinoma at the site of previous sporotrichosis. (26th September 2019) - Ji, Yong‐Zhi; Ma, Zhi‐Ming; Chang, Li; Liu, Shi‐Rui
Abstract: Background: Cutaneous squamous cell carcinoma (cSCC) is a malignant tumor of epithelial keratinocytes, with a relatively reduced frequency of lymph node metastasis. Despite the fact that this tumor type is largely preventable, the incidence of cSCC is rising every year. Ultraviolet exposure is a major cause of cSCC and directly contributes to cSCC. Other known environmental risk factors include ionizing radiation, cigarette smoking, and certain chemical exposures. Aims: In this study, we report a clinical case of cSCC with a novel causative factor. Patient/Methods: The report describes a 72‐year‐old male who was seen for a dermatosis condition initially. Later, epidermal hyperplasia and granulomatous inflammation of the dermis was diagnosed based on skin biopsy. Fungal culture revealed the presence of Sporothrix schenckii which led to the diagnosis of fixed‐type sporotrichosis. Results: Four months of oral terbinafine (250 mg once a day) administration partially resolved the lesions. Patient was subsequently diagnosed with cSCC, and surgical resection with wider margins was performed. Conclusion: After a careful and rigorous exclusion of known risk factors, we confirmed that this incidence of cSCC was caused by chronic inflammation which followed fixed‐type sporotricosis.